Improvement in phloroglucinol compound extracted from different parts of Eugenia umbelliflora monitored by LC-UV and antimicrobial activity. Issue 14 (15th July 2022) - Farias, Ingrid Vicente; Amorim, Clarissa Medeiros de; Graff, Eliane; Breia, Isabel; dos Santos, Matheus Corrêa; Norberto, Silvana; Faqueti, Larissa G.; Bresolin, Tania Mari Bellé; Bella Cruz, Alexandre; Meyre-Silva, Christiane
Abstract: The phloroglucinol eugenial C, eugenial D and eugenial E are the main active compounds in Eugenia umbelliflora fruits. This study aims to evaluate the extraction conditions of E. umbelliflora, using ethanol as solvent, focusing on the phloroglucinol and antimicrobial activity. In order to optimize the extraction conditions, ethanol 50, 70 and 90 o GL was used as a solvent in the proportions of 1:20 (w/v) of drug:solvent ratio (D:S), stirring (330 rpm) at room temperature during 4 h, monitored by LC-UV and antimicrobial assay. The LC-UV method developed was linear over a concentration range of 3.4–68.0, 5.3–106.0 and 5.0–100.8 μg.mL −1 of eugenial C, eugenial D and eugenial E, having LOQ of 1.68, 1.33 and 0.8 μg.mL −1, respectively. The fruits showed the best herbal raw material and showed the highest phloroglucinol concentration and activity against S. aureus, when extracted with ethanol 90 o GL, during 4 h, at 1:20 of D:S. Graphical Abstract: UF0001